AN ANALYSIS OF DERIVATIONAL AFFIXES FOUND IN THE JAKARTA POST NEWSPAPER - I Made Kein Windiatmika; Ni Putu Cahyani Putri Utami (Universitas Warmadewa, 2023)
This study focused to analyse derivational affixes found in the Jakarta Post Newspaper. To describe the data source this study used the qualitative method. The observation method is used in this study to collect the data. There were several steps to collecting the data which were, first finding the data on the Jakarta Post website, second reading and underlining all the words containing derivational affixes, and then identifying and classifying based on their categories. This study used the theory proposed by Lieber (2009) as the main theory and supported theory by Katamba (1993) and Plag (2002). This study used formal and informal methods to present the data. After analyzing the data source there are two types of derivational affixes, namely derivational prefixes and derivational suffixes. There were 36 data of derivational affixes found in three newspaper such as 6 data are prefixes -un, -non, -over -ir 16,6% and 30 data are suffixes -y, -ity, -er, -ion, -ly, -al, -ful, -ible -or with percentage 83,4%. Based on the result it can be concluded the derivational suffix is more dominant than the derivational prefixes found in the Jakarta Post newspaper Keywords: derivation; Jakarta post Newspaper; prefix; suffix